A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE, RECOUNT, AND NARRATIVE TEXTS AT SMA NEGERI 5 PEKANBARU - IIP KURNIAWAN; ELIWARTI ELIWARTI; RUMIRI RUMIRI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study is to find out the ability of the second year students’ reading comprehension of descriptive, recount, and narrative texts at SMAN 5 Pekanbaru. This research was conducted at the State Senior High School 5 Pekanbaru from July to November 2017.The population was all of the second year students in academic year of 2017/2018. The number of the entire population was 431. The researcher used cluster-sampling technique to determine the sample. The participant of this research was 39 students of XI.IA5 class. This research focuses on students’ comprehending descriptive, recount, and narrative texts in terms of finding the main ideas, factual information, the meaning of vocabulary, identifying references and making inferences. The data were collected using reading test with multiple choice type. The test contained 48 items. The tryout was conducted to check the validity and reliability of the test. From the results, it was found out that first: the real condition of the second year students of the State Senior High School 5 Pekanbaru in reading comprehension ability is in good level. It can be seen from the mean score of the students, which is 71. The students’ scores were good in general; specifically they were excellent in three components, namely finding main idea, guessing vocabulary, and finding language features. They were also good in three components, namely finding factual information, identifying reference, finding social function. There were only two components in mediocre level, namely making inference, and finding generic structure. Further, it was suggested that the students need to improve their reading comprehension ability by practicing more on reading exercise and should motivate themselves to read more reading materials. This research can be also used as a reference to conduct further studies related to reading comprehension ability.Keywords: Study, Ability, Descriptive Research, Reading Comprehension, Descriptive Text, Recount Text, Narrative Text.